Prediction Variables for District Operating Expenditure Per Pupil in the State of Illinois - Mary M. Polite (Educational Considerations, 1992)
The influence of demographic and social variables indicate that perhaps it is time once again for Illinois to consider a cost-of-education index in the school funding formula.